Sosialisasi Pembuatan Bakteri Fotosintesis sebagai Penyubur Tanaman : Socialization of Making Photosynthetic Bacteria as Plant Fertilizer - Jismi Mubarrak; Rena Lestari; Rio Karno; Arief Anthonius Purnama; Eti Meirina Brahmana; Dahlia Dahlia (Institut Riset dan Publikasi Indonesia, 2022)
This service activity aims to increase students' knowledge about photosynthetic bacteria as plant fertilizers, so that they can increase student awareness to increase knowledge and it is hoped that knowledge can be used as capital for entrepreneurship. This activity also provides knowledge about photosynthetic bacteria starting from the understanding, characteristics to the working mechanism of bacteria. Methods and techniques of socialization consist of: planning, action and reflection. In planning, the preparation and dissemination of activities were carried out, at the action stage, the service was carried out starting with the exposure of photosynthetic bacteria, the working mechanism of bacteria and their benefits as plant fertilizers, and a question and answer session was held. The next stage is reflection, which is done by analyzing the participants' responses to the activities that have been carried out. In this service activity, the students were enthusiastic.